Feasibility of fetal cardiac output measurement by phase-contrast magnetic resonance imaging using Doppler ultrasound gating increases with gestational age - Signe Gade Hellmuth; Ditte Staub Jørgensen; Kasper Gadsbøll; Caroline Taksøe-Vester; Ann Tabor; Olav Bjørn Petersen; Niels Vejlstrup (Journal of Cardiovascular Magnetic Resonance, 2025)
ABSTRACT: Background: Fetal cardiovascular magnetic resonance (CMR) is a valuable tool for assessing fetal blood flow; however, its use has primarily been focused on near-term pregnancies. This study aimed to evaluate the feasibility of Doppler ultrasound-gated two-dimensional (2D) phase-contrast CMR of the human fetus in the early, mid, and late third trimester. Methods: A total of 100 fetal MRI scans were performed at gestational age (GA) 28, 32, and 38 weeks in 38 fetuses with (n = 13) and without (n = 25) congenital heart defects. Combined ventricular output was measured by Doppler ultrasound-gated 2D phase-contrast CMR in the ascending aorta and main pulmonary artery. Success rate of acquisition, repeatability of phase-contrast measurements, and intra-/interobserver agreement were assessed at each GA. Results: Combined ventricular output was obtained in 76/100 (76%) scans. The success rate of acquisition improved with increasing GA from 15/34 (44%) at GA 28 weeks to 31/35 (89%) at GA 32 weeks (p < 0.001 compared to 28 weeks) and 30/31 (97%) at GA 38 weeks (p < 0.001 compared to 28 weeks). Repeatability of phase-contrast measurements demonstrated a moderate to strong correlation (r = 0.63–0.82, p = 0.002), with no significant bias but wide limits of agreement. The mean difference ±95% limits of agreement were 7.3 ± 245 mL/min, −13.0 ± 260 mL/min, and −3.9 ± 326 mL/min at 28, 32, and 38 weeks, respectively. Conclusion: Feasibility of fetal CMR improves with increasing GA. While Doppler-gated 2D phase-contrast CMR can effectively assess fetal combined ventricular output and allows for in-group comparisons, the precision may still be insufficient for clinical application.